Suudi Arabistan ve Türkiye ticari ilişkileri (2000 – 2015) - Öztürk, MustafaYazar (My University, 2017)
2000-2015 yılları arasındaki dönemde incelenmesi çalışmanın amacını meydana getirmektedir. Ulaşılan sonuçlara göre Türkiye ve Suudi Arabistan ticari ilişkileri gün geçtikçe daha iyiye gitmektedir ve incelenen 15 yıllık sürede iki ülke arasındaki ticaret hacmi yaklaşık 5 kat artmıştır.

The study of commercial relations between Turkey and Saudi Arabia during the period between the years 2000-2015 is the reason for this study. According to the results, commercial relations between Turkey and Saudi Arabia is improving day by day and the trade volume between the two countries has been increased 5 times in the 15 years examined.
Keywords: Commercial Relations; Dış ekonomik ilişkiler; Ekonomi politikası- Türkiye; Middle East; Orta Doğu; Saudi Arabia; Suudi Arabistan; Tarih; Ticari İlişkiler Turkey; Türkiye